Exporting Educational Change: Unexamined Assumptions (LEARNing Landscapes, 2023)
This paper takes a philosophical look at what it means to talk about educational change in the context of the global proliferation of Western secular liberal democratic values. A handful of challenges, contradictions, and incoherencies that potentially impede the success of educational change projects in developing countries are examined with a view to furthering discussion about what vision of the learner and society they promote, either implicitly or through taken-for-granted assumptions. Politics, leadership, and timelines become impediments to real change. Brief reference is made to these concepts. The author provides examples from 10 years of international curriculum work on several continents in an attempt to highlight some of the latent irregularities that impede the progress of educational change endeavors.
Keywords: curriculum reform; values; secularism; educational change; liberalism